2007
DOI: 10.1590/s1415-47572007000100013
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype characterization of Crotalaria juncea (L.) by chromosome banding and physical mapping of 18S-5.8S-26S and 5S rRNA gene sites

Abstract: The chromosomes of Crotalaria juncea, a legume of agronomic interest with a 2n = 16 karyotype composed of metacentric chromosomes, were analyzed using several cytogenetic techniques. C-banding revealed heterochromatic regions around the centromeres in all chromosomes and adjacent to the secondary constriction on the chromosome 1 short arm. Fluorescent staining with the GC-specific chromomycin A3 (CMA) highlighted these heterochromatic regions and a tiny site on the chromosome 1 long arm while the AT-specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
2
25
0
6
Order By: Relevance
“…In situ hybridization was carried out as previously described (Mondin et al, 2007). Briefly, the probe used for 45S rDNA localization was the 9.1-kb maize 45S rDNA repeating unit labeled with biotin-14-dATP by nick translation (Bionick Labeling System, Invitrogen, USA).…”
Section: Pizzaia Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In situ hybridization was carried out as previously described (Mondin et al, 2007). Briefly, the probe used for 45S rDNA localization was the 9.1-kb maize 45S rDNA repeating unit labeled with biotin-14-dATP by nick translation (Bionick Labeling System, Invitrogen, USA).…”
Section: Pizzaia Et Almentioning
confidence: 99%
“…The probe (5 ng/µL) was added to the hybridization mixture and denatured by heating at 95°C for 10 min, cooled and dropped onto the slide preparation that was denatured in a thermocycler at 92°C for 10 min. Hybridization was then carried out at 37°C for 20 h. Post-hybridization steps followed the protocol previously described by Mondin et al (2007). The slides were counterstained with 1 µg/mL DAPI in Vectashield (Vector, USA).…”
Section: Pizzaia Et Almentioning
confidence: 99%
“…Esto sugiere que, a pesar de la similitud en la morfología cariotípica de las especies de Canna, el bandeo DAPI podría detectar la variación interespecífica en la distribución cromosómica de la heterocromátina e identificar pares cromosómicos. Este método permitirá avanzar con la caracterización citogenética de estas especies ya que ha dado buenos resultados en una amplia variedad de géneros tales como Zea L. (González & Poggio 2011, González et al 2013, Fourastié 2015, Citrus L. (Guerra 1993), Crotalaria L. (Mondin et al 2007) y Opuntia Mill. (Realini et al 2014), entre otros.…”
Section: Resultados Y Discusiónunclassified
“…Our group has used this strategy to determine the karyotype of Stylosanthes (VIEIRA et al, 1993) and Passiflora species (CUCO et al, 2005) as well as for Crotalaria juncea (MONDIN et al, 2007). For this reason, we may speculate here that the variation observed in chromosome 2 is due to a shift of the centromere segment.…”
Section: Discussionmentioning
confidence: 99%
“…Two kinds of events could explain the non-observation of satellites in metaphase chromosomes: the satellites are in the telomeric region or the expression of nucleolar-organizing regions is not sufficient to result in secondary constriction or satellite formation. In Crotalaria juncea, for instance, Mondin et al (2007) showed that a NOR site was positive but no secondary constriction was visualized at metaphase, the chromosome morphology remaining unmodified.…”
Section: Discussionmentioning
confidence: 99%